Izid rehabilitacije pri pacientih po obojestranski amputaciji spodnjega uda - Petkovšek Gregorin, Romana (Rehabilitacija (Ljubljana), 2012)
Introduction: The level of amputation is an important factor in predicting outcome of rehabilitation and fitting with prosthesis. Other important factors include age, accompanying diseases and the cause that led to amputation. The aim of our study was to evaluate the success of rehabilitation of patients after bilateral lower limb amputation. Methods: A retrospective quantitative study was conducted. Data were collected from medical documentation on all inpatients after bilateral lower limb amputation during period was January 2006 to December 2010 at the University Rehabilitation Institute in Ljubljana. They were assessed using the motor sub-score of the Functional Independence Measure (FIM). Results: Statistically significant progress in motor FIM from admission to discharge was observed in below-knee amputees throughout the study period, as well as in amputees with one below-knee and one above-knee amputation (just to a lesser extent). In bilateral above-knee amputees the progress was not statistically significant (except in the year 2010). Conclusion: In general, the results suggest that patients after bilateral lower limb amputation improve their ambulation and selfcare ability after rehabilitation.
Keywords: amputacija; Amputation; Lower extremity; Outcome assessment (health care); rehabilitacija; Rehabilitation; spodnja ekstremiteta; spodnji ud; vocational rehabilitation